Relationship between psychological characteristics, personality traits, and training on performance in a neonatal resuscitation scenario: A machine learning based analysis - Giordano, V.; Bibl, K.; Felnhofer, A.; Kothgassner, O.; Steinbauer, P.; Eibensteiner, F.; Gröpel, P.; Scharnowski, F.; Wagner, M.; Berger, A.; Olischar, M.; Steyrl, D. (Frontiers in Pediatrics, 2022)
Background: In life-threatening emergency events, prompt decision-making and accurate reactions are essential for saving a human’s life. Some of these skills, such as team communication, resource management or taking a team time out, can be improved by regular simulation trainings. However, besides these factors, individual characteristics may play a significant role in the patients´ outcome after a resuscitation event. This study aimed to differentiate personality characteristics of team members who take responsibility for their actions, contextualizing the effect of training on resuscitation performance. Methods: Six hundred and two third-year medical students were asked to answer psychological and personality questionnaires. Fifty-five of them performed in a neonatal simulation resuscitation scenario. A machine learning design was utilized to better understand the interaction of psychological characteristics and training. The first model aimed to understand how to differentiate between people who take responsibility for their actions versus those who do not. In a second model, the goal was to understand the relevance of training by contextualizing the effect of training to other important psychological and personality characteristics like locus of control, anxiety, emotion regulation, openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism. Results: Anxiety and gender were the most important factors associated with taking responsibility for an action. Training was the most relevant factor in terms of performance during a neonatal resuscitation scenario. Conclusion: Training had a significantly stronger effect on performance in medical students in a neonatal resuscitation scenario than individual characteristics such as demographics, personality, and trait anxiety.